Analysis and prediction of 5-year survival in patients with cutaneous melanoma: a model-based period analysis - Zheng, Suzheng; Yu, Hai; Zheng, Xinkai; Wu, U Tim; Ming, Wai-kit; Huang, Hui; Song, Jiaxin; Zhang, Xiaoxi; Lyu, Jun; Deng, Liehua (Frontiers in Endocrinology, 2023)
Background The survival and prognosis of patients are significantly threatened by cutaneous melanoma (CM), which is a highly aggressive disease. It is therefore crucial to determine the most recent survival rate of CM. This study used population-based cancer registry data to examine the 5-year relative survival rate of CM in the US. Methods Period analysis was used to assess the relative survival rate and trends of patients with CM in the Surveillance, Epidemiology, and End Results (SEER) database during 2004-2018. And based on the data stratified by age, gender, race and subtype in the SEER database, a generalized linear model was established to predict the 5-year relative survival rate of CM patients from 2019 to 2023.The 5-year relative survival increased to various degrees for both total CM and CM subtypes during the observation period. The improvement was greatest for amelanotic melanoma, increasing from 69.0% to 81.5%. The 5-year overall relative survival rates of CM were 92.9%,